HOSPITALISATION FOR MYASTHENIA: ARE WE DOING SOMETHING WRONG?. Issue 10 (9th September 2014) - Sussman, Jon; Ortiz, Magdalena Niestrata
Abstract : Patients with autoimmune MG may deteriorate despite treatment. We analysed the symptomatology and management of 78 patients with 108 admissions from 2002–2012. Despite mean time from deterioration to admission of 50 days, in 45%, treatment was unchanged. In 55%, Prednisolone was increased by only 0.29 mg/kg. Pyridostigmine was increased by 206.667 mg. In 20%, only pyridostigmine was increased. Of patients with bulbar involvement at diagnosis, 45.95% had received no immunosuppression by admission; 35.14% received low doses despite grade III-V disease. Of patients treated for six months prior to admission, 43% receiving no steroid-sparing agents and 16.22% a low dose. Doses were increased slowly and inconsistently. Of patient requiring ICU admissions, 75% were receiving no steroid-sparing agents despite being treated for at least 6 months before hospitalisation. Of patients with multiple admissions, 33% were not receiving steroid-sparing agents. Of the remaining patients, 39% were receiving a low dose despite being treated for at least 6 months. Non-myasthenologists appear overcautious with all treatments but especially steroids. MG is frequently sub-optimally managed, possibly contributing to hospital admission. There is a need for authoritative evidence-based guidelines conformed by trials. The authors will discuss developments in this direction.